1987
DOI: 10.1016/s0010-9452(87)80044-8
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Aphasia and Global Aphasia in Left Brain-Damaged Patients

Abstract: Two hundred and twenty three right-handed patients consecutively admitted to the wards in a 21-month period for a left-sided cerebrovascular disease were examined 15 to 30 days after the stroke for the presence of aphasia. Twenty-seven of them could not be assessed. Of the remaining 196, 108 (55.1%) were aphasic. The incidence of global aphasia (43%) in the latter group was higher than in previous studies. Based on CT-scan data it was associated in 32% of patients with a deep lesion and only in 53% with an ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…35,36 Female gender was not an independent risk factor for aphasia resulting from FEIS. This finding is in line to the majority of aphasia studies 13,20,37 but is in contrast to 2 stroke databank studies. 17,38 Neither gender nor age had an influence on severity or fluency of aphasia, which is in line with the majority of aphasia studies.…”
Section: Discussionsupporting
confidence: 87%
“…35,36 Female gender was not an independent risk factor for aphasia resulting from FEIS. This finding is in line to the majority of aphasia studies 13,20,37 but is in contrast to 2 stroke databank studies. 17,38 Neither gender nor age had an influence on severity or fluency of aphasia, which is in line with the majority of aphasia studies.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, a difference between sexes for aphasia score (in the opposite direction: more women having aphasia) just reached significance in the univariate analysis, but this difference disappeared in the multiple regression analysis. A number of previous studies found no relation between sex and aphasia (1,21,25, 261, but did not control for covariates. A case-based stroke data bank study [27} had a result similar to ours; it found univariately a higher rate of aphasia in women, a difference that disappeared when analyses included covariates.…”
Section: Discussionmentioning
confidence: 87%
“…The MPT results in a loss of mitochondrial membrane potential and in a decrease of ATP production. It is now known that the MPT is not a consequence of nonspecific mitochondrial membrane damage, but instead the result of the opening of membrane channels, the so called permeability transition pores (PTP) [33,34], which are inhibited by the immunosuppressant cyclosporin A (CsA) [35].…”
Section: Moderate Mitochondrial Camentioning
confidence: 99%